Business Model Canvas (BMC) And Value Proposition Canvas (VPC) Analysis For Whale Shark halal Tourism, Tarano District, Sumbawa Regency Solution To Formulate A Strategy To Increase Tourism Value - Maradita, Fendy; Aprirachman, Rozzy (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to find strategies to increase the value of Whale Shark tourism in Labuhan Jambu Village, Tarano District by using the perspective of whale shark tourism managers and related stakeholders using the Business Model Canvas (BMC) approach through nine channels. This study also looks at tourism value from a consumer perspective through the Value Proposition Canvas (VPC) approach from two aspects, namely the customer profile and value proposition. The sampling technique in this study used the Snawbal Sampling technique by identifying, selecting, and taking samples in a network or continuous chain of relationships. Meanwhile, data analysis used the Miles and Huberman technique which included data reduction, data presentation and conclusion. The results of this research to increase the value of Whale Shark tourism in Labuhan Jambu Village based on the BMC approach areThe whale shark tourism market segmentation is foreign tourists, domestic tourists anddiving/snorkeling enthusiasts, consist of online promotions via social media Instagram, direct promotions, participating in national events, whale shark festivals and collaboration with tour guides and travel tours, the major key partnership to maintain is travel agents, tour guides, fishermen, bagang owners, restaurants and hotels and the important Key resources consist of whale sharks, tour operators, supporting facilities and the Labuhan Jambu village community. Meanwhile the VPC results to solved the cunsomer provile including increasing Products and services for whale shark tourism are that visitors can see and swim directly with whale sharks, unique and rare tours, optimal service to visitors, provision of speed boats and complete diving/snorkeling equipment for visitor satisfaction.Pain Relievers consists of providing regular information about the appearance of whale sharks, limiting swimming time with whale sharks, providing speed boat access from Labuhan Jambu village, periodic efforts and programs to support whale shark conservation.Gain creators consist of tour packages and equipment for swimming with whale sharks, providing education on whale shark tourism to tourists, maintaining visitor trust by providing optimal service and mapping optimal times to meet whale sharks to inform tourists and related parties.